2020
DOI: 10.3390/md18040179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Allelochemical Activity and Biochemical Profile of Different Phenotypes of Picocyanobacteria from the Genus Synechococcus

Abstract: Organisms belonging to Synechococcus sp. genera are observed in all freshwater, brackish, and marine waters of the world. They play a relevant role in these ecosystems, since they are one of the main primary producers, especially in open ocean. Eventually, they form mass blooms in coastal areas, which are potentially dangerous for the functioning of marine ecosystems. Allelopathy could be an important factor promoting the proliferation of these organisms. According to the authors’ best knowledge, there is no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Recently, Kovács et al [17] demonstrated that the freshwater picocyanobacterium C. gracile had a substantial negative impact on the coexisting S. quadricauda. Konarzewka et al [26] also showed strong inhibition of Chlorophyceae growth due to exudates from three different Synechococcus phenotypes. Similar observations have been also made for other picocyanobacterium Synechocystis sp.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recently, Kovács et al [17] demonstrated that the freshwater picocyanobacterium C. gracile had a substantial negative impact on the coexisting S. quadricauda. Konarzewka et al [26] also showed strong inhibition of Chlorophyceae growth due to exudates from three different Synechococcus phenotypes. Similar observations have been also made for other picocyanobacterium Synechocystis sp.…”
Section: Discussionmentioning
confidence: 96%
“…That study pointed to the diatoms of the genera Navicula, Chaetoceros, Amphora, Coscinodiscus, Grammatophora, and Nitzschia as the most allelochemical-sensitive organisms. Moreover,Śliwińska-Wilczewska and Latała [23],Śliwińska-Wilczewska et al [24], and Konarzewska et al [26] demonstrated that the addition of Synechococcus sp. filtrate strongly inhibited the growth of Skeletonema marinoi Sarno and Zingone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinction between the three main identified phenotypes of the genus Synechococcus is based on the phycobilin pigments composition [ 20 , 21 ]. Six et al [ 22 ] in their research presented a classification that divides marine Synechococcus to Type 1, Type 2, and Type 3.…”
Section: Introductionmentioning
confidence: 99%